The old oak [videorecording (DVD)] - Fenton, George (Zeitgeist Films, Kino Lorber, 2024)
The Old Oak is the last pub standing in a once thriving mining village in northern England and a gathering space for a community that has fallen through hard times. There is growing anger, resentment, and a lack of hope among the residents, but the pub and its proprietor TJ are a fond presence to their customers. When a group of Syrian refugees move into the floundering village, a decisive rift fueled by prejudices develops between the community and its newest inhabitants. The formation of an unexpected friendship between TJ and a young Syrian woman named Yara opens up new possibilities for the divided village.